2012
DOI: 10.1016/j.nbd.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Post mortem cerebrospinal fluid α-synuclein levels are raised in multiple system atrophy and distinguish this from the other α-synucleinopathies, Parkinson's disease and Dementia with Lewy bodies

Abstract: Differentiating clinically between Parkinson's disease (PD) and the atypical parkinsonian syndromes of Progressive supranuclear palsy (PSP), corticobasal syndrome (CBS) and multiple system atrophy (MSA) is challenging but crucial for patient management and recruitment into clinical trials. Because PD (and the related disorder Dementia with Lewy bodies (DLB)) and MSA are characterised by the deposition of aggregated forms of α-synuclein protein (α-syn) in the brain, whereas CBS and PSP are tauopathies, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 33 publications
1
81
1
1
Order By: Relevance
“…This proposal provides a guide for directing efforts towards the isolation of the toxic forms α-syn in vivo. As such, it would be highly desirable to obtain more comprehensive information about α-syn oligomers that have been detected in the cerebrospinal fluid and sera of PD patients [13][14][15][16] through the epitope mapping used here. The challenge will remain to isolate oligomers from clinical specimens of PD patients or other biological systems under near-native conditions [57,58] and elucidate how the oligomers produced in vivo compare with those observed here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This proposal provides a guide for directing efforts towards the isolation of the toxic forms α-syn in vivo. As such, it would be highly desirable to obtain more comprehensive information about α-syn oligomers that have been detected in the cerebrospinal fluid and sera of PD patients [13][14][15][16] through the epitope mapping used here. The challenge will remain to isolate oligomers from clinical specimens of PD patients or other biological systems under near-native conditions [57,58] and elucidate how the oligomers produced in vivo compare with those observed here.…”
Section: Discussionmentioning
confidence: 99%
“…α-Syn is expressed as an intracellular protein but has been shown to be directly secreted or released as a result of neuronal death or stress conditions into the extracellular space [12]. Soluble oligomeric forms of α-syn have also been detected in the cerebrospinal fluid and sera of PD patients [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The source of PDlinked AS in human CSF remains unknown, but recent studies suggest that despite the higher levels in peripheral blood products, neurons in the CNS represent the principal source of AS in human CSF [790]. Postmortem CSF levels of oligomeric AS and pAS significantly raised in MSA compared to other controls and other synucleinopaties, but did not distinguish PD and DLB from PSP or control groups [791]. CSF AS levels did not differ significantly between DLB and/or PD and AD [792], but AS levels were reduced in DLB patients with long disease duration or worse cognitive performance [760,792].…”
Section: α-Synuclein As a Biomarker For Synucleinopathiesmentioning
confidence: 90%
“…As such, it may be beneficial in the diagnosis of PD but not for MSA. Also, Foulds et al (2012) detected levels of total and oligomeric forms of α-syn as well as phosphorylated and phosphorylated oligomeric forms of α-syn in CSF samples from patients with PD, MSA, DLB, and PSP and healthy controls. They found that, of the four forms of α-syn, only the oligomeric phosphorylated forms of α-syn in CSF could differentiate MSA from PD.…”
Section: α-Synmentioning
confidence: 96%